Introduction Integrative Analysis of Hepatic Progenitor Cell Activation in Primary Biliary Cholangitis Using Immunohistochemistry, Flow Cytometry, and LGR5 Gene Expression Profiling - Dr.Inas Abd Al Majed Rasheed; Dr.Ahmed Salim Khazaal (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Primary Biliary Cholangitis (PBC) is an autoimmune liver disorder with progressive cholangitis resulting from destruction of intrahepatic bile ducts. Fundamentally, hepatic progenitor cells or oval cells have significant roles in liver regeneration, as well as in the pathogenesis of PBC. Knowledge on HPC activation and changes in LGR5 gene expression in PBC can be useful in elucidation of disease processes and identification of potential therapeutic interventions. Objectives: The purpose of this research was to compare the activation of HPC in PBC patients to that in non-PBC subjects, influence of HPC on PBC pathogenesis, by immunohistochemistry, flow cytometry and LGR5 gene expression analysis. Methods: The study design used was prospective cross-sectional which compared PBC patients to non-PBC controls. For identification of HPC markers, immunohistochemical staining of the tissue samples with CK19 and EpCAM antibodies was used; circulating HPC isolation was performed by flow cytometry; and real-time PCR was used for LGR5 gene expression measurement. Results: The PBC patients revealed a potential of HPC activation to a significantly higher degree as compared to the non- PBC controls, based on over expression of CK19 and EpCAM and higher LGR5 expression. These findings were further supported by flow cytometry data that demonstrated a higher percentage and absolute number of HPCs in liver tissue of PBC patients. Conclusion: The present work adds evidence to suggest that enhanced levels of HPC and LGR5 might contribute to PBC development. Interestingly, these findings imply the utilization of HPC markers as diagnostic and prognostic biomarkers as well as providing information about molecular therapeutic targets for PBC.